From Stigma to Support: Evaluating Public Perceptions of Mental Health for Improved Healthcare Management - Raikhola, Pushkar Singh (People’s Journal of Management, 2025)
Background: Public perceptions of mental health play a critical role in shaping stigma, help-seeking behaviors, and societal support for individuals with mental health disorders. Despite increasing awareness, misconceptions and stigmatizing attitudes persist, necessitating updated assessments of contemporary attitudes. Objective: This study aimed to evaluate current public perceptions of mental health, focusing on stigma, functional capabilities of individuals with mental illness, and demographic differences in attitudes. Methods: A cross-sectional survey was conducted (N=196), analyzing responses using one-sample t-tests (neutral midpoint = 3), chi-square goodness-of-fit tests, independent samples t-tests (gender differences), and ANOVA (information source effects). Findings: Respondents strongly rejected overtly stigmatizing labels (e.g., "crazy," *p* < .001) but endorsed blame attribution (M diff = +1.107, *p* < .001). Most agreed that mental health problems often go undetected (86.2%) and can occur at any age (79.6%). No gender differences were found (*p* = .839), but perceptions varied significantly by information source (F = 3.00, *p* = .02), with formal education linked to more positive views than social media. Conclusion: While progress is evident in reducing explicit stigma, subtle misconceptions persist, particularly around personal responsibility for mental illness. Interventions should prioritize nuanced education, leveraging credible information sources to address enduring biases. Novelty: This study highlights the divergence between rejection of overt stigma and persistence of implicit biases, while identifying information sources as a modifiable factor shaping attitudes.